1978
DOI: 10.1126/science.202.4365.305
|View full text |Cite
|
Sign up to set email alerts
|

North American Pleistocene Stages Reconsidered in Light of Probable Pliocene-Pleistocene Continental Glaciation

Abstract: Confusion due to the conceptual usage of classic North American Pleistocene stage terms indicates the need for a new or revised terminology. The Pliocene-Pleistocene boundary has tentatively been dated about 2.5 +/- 0.1 x 10(6) years. Glacial deposits in the central United States older than about 2.2 x 10(6) years may span that boundary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 4 publications
1
50
0
1
Order By: Relevance
“…Most hypotheses for the origin of the MPT invoke a response to a long-term cooling, possibly induced by decreasing atmospheric pCO 2 (Raymo, 1997;Paillard, 1998;Berger et al, 1999;Tziperman and Gildor 2003). None of these hypotheses, however, accounts for the geological constraint that the earliest Northern Hemisphere ice-sheets covered a similar or larger area than those that followed the MPT (Boellstorf, 1978;Roy et al, 2004a;Balco et al, 2005). Given that the MPT was associated with an increase in ice volume, this constraint requires that post-MPT ice sheets were substantially thicker than pre-MPT ice sheets, indicating a change in subglacial conditions that influence ice dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most hypotheses for the origin of the MPT invoke a response to a long-term cooling, possibly induced by decreasing atmospheric pCO 2 (Raymo, 1997;Paillard, 1998;Berger et al, 1999;Tziperman and Gildor 2003). None of these hypotheses, however, accounts for the geological constraint that the earliest Northern Hemisphere ice-sheets covered a similar or larger area than those that followed the MPT (Boellstorf, 1978;Roy et al, 2004a;Balco et al, 2005). Given that the MPT was associated with an increase in ice volume, this constraint requires that post-MPT ice sheets were substantially thicker than pre-MPT ice sheets, indicating a change in subglacial conditions that influence ice dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Because chemical weathering involves the removal of the more reactive mineral species, resulting in a composition that reflects the more resistant minerals as well as the products of chemical weathering of the more reactive species, sediments derived from regolith will have a different mineralogical and geochemical signature than sediments derived from fresh crystalline bedrock. Such a distinction is seen in tills from the North American mid-continent, where Boellstorf (1978) first noted that the oldest (unweathered) tills (42 Ma) are enriched in stable minerals and weathered products and depleted in unstable minerals compared to younger tills. Roy et al (2004a, b) found similar first-order mineralogical changes as well as geochemical changes in the silicate fraction of midcontinent tills that further indicated a temporal change from a regolith to an unweathered bedrock source.…”
Section: The Regolith Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Ice deformation is calculated from horizontal stress according to Glen's flow law. Early Pleistocene ice sheets may have been as spatially expansive as during the late Pleistocene [Boellstorff, 1978;Fisher et al, 1985;Joyce et al, 1993] (but see Barendregt and Irving [1998] Figures 3c and 3e). A possible resolution is that a deformable bed underlaid the Laurentide during the early Pleistocene and led to faster flowing, more expansive, and thinner ice sheets [Fisher et al, 1985;Beget, 1986;Alley, 1991;Clark and Pollard, 1998].…”
Section: Model Descriptionmentioning
confidence: 99%
“…[33] Another shortcoming is that the maximum equatorward extent of the model ice sheet is only 60°N whereas ice sheets seem to have reached into Iowa and Nebraska (40°N, [Boellstorff, 1978;Barendregt and Irving, 1998]) and there are indications that the Laurentide repeatedly entered the Mississippi River drainage basin during the early Pleistocene [Joyce et al, 1993]. Perhaps the glacial cycles generated by this model represent a simple prototype, but other mechanisms associated with trends toward increasing asymmetry, larger amplitude and longer period glacial cycles and episodes of more southerly glacial extent must also be present.…”
mentioning
confidence: 99%